Method of Predicting, Estimating and Improving Mean Time between Failures in Reducing Reactive Work in Maintenance Organization - M. M., Noor; K., Kadirgama; E. H., Jamaluddin; M. M., Rahman (Universiti Malaysia Pahang, 2009)
Mean time between failures (MTBF) is a simple way of quantifying a repairable system, subsystem, or component’s reliability. MTBF has been used for various decisions. Reliability of the system quantitatively determine by MTBF. Mathematical approach in quantifying MTBF is being used. Poisson distribution, Weibull model and Bayesian are the most popular approach used in developing MTBF model. MTBF is often confused with mean time to failure (MTTF), which MTTF applies to replaceable, rather than repairable. In current situation, most products designed as non-repairable unit, thus will eliminate varies level of repairing quality due to human error or level of competencies. This paper will explains the underlying complexities and misconceptions of MTBF and clarify in sequence what are the items and concerns that need to be consider in estimating MTBF.